Developing Maritime Management Curricula: Aligning Industry-Specific Needs with Sustainability and Emerging Technologies - Hotman Tua Pangaribuan; Imam Fahcruddin; Faisal Aswin; April Gunawan Malau; Hendrawan Hendrawan (Digital Innovation : International Journal of Management, 2024)
The maritime industry is rapidly evolving due to technological advancements and increased emphasis on sustainability. This research aims to develop a specialized maritime management curriculum that aligns with the needs of the port, shipping, and logistics sectors while incorporating emerging technologies and sustainability practices. Through qualitative research involving 5 maritime professionals, 5 lecturers, and 5 graduates, this study investigates the current gaps in maritime education and the essential competencies needed in modern maritime professions. Using descriptive analysis, the research provides insights into the integration of applied management studies, technical skills, and innovation into the curriculum. The study identifies key areas where existing curricula fall short, including the underrepresentation of technological and sustainability competencies. By examining the experiences of industry professionals and educational experts, a new curriculum framework is proposed, aiming to enhance graduate readiness for modern challenges. The curriculum effectiveness is evaluated using key performance indicators (KPIs), with a 9/10 score on alignment with industry needs. Comprehensive tables illustrate the scoring across various curriculum components, including technology integration, sustainability, and managerial skills. The findings suggest that the proposed curriculum model can significantly improve the employability of graduates, ensuring that they are equipped to meet the dynamic requirements of the maritime industry. Continuous curriculum development, with feedback from industry stakeholders, is recommended to maintain alignment with evolving industry needs.